The voice of principals: interviews with representatives of unions and organizations involved in school management. - Venzalá, José Francisco; Gutiérrez Morillo, Alonso; Martín Ramos, Eusebio; Gutiérrez Gutiérrez, Mario; Fernández Martínez, Alfonso; Delgado Marín, Jorge; Villalba Cabrera, Fernando; Loranca Irueste, Maribel; Valero Marrón, José Luis (Avances en Supervisión Educativa, 2024)
Interviews on school management in Spain made to the following associations and unions related to education and its management: ANPE (National Association of Teaching Professionals); CCOO-FE (Education Federation of Comisiones Obreras); CGT (Education Federation of Confederación General de Trabajadores); CSIF (Independent and Civil Servants Union); FEAE (Federation of the European Forum of Education Administrators); FEDEIP (Federation of Principals and Managers of Public Pre-school and Primary Education Centers); STEs-Intersindical (Union of Education Workers); UGT-SP (General Union of Workers).
Keywords: School management; leadership; professional associations; teachers' unions; Spain